Appearances Can Be Deceiving Transformation and Identity in 2 Corinthians 11.13–15 - Carr, Frederick David 1983- (2025)
In 2 Corinthians 11.13–15, Paul uses the verb μετασχηματίζω in the middle voice to claim that his opponents are, in the NRSV’s rendering, ‘disguising themselves as apostles of Christ’. Yet one could more literally translate the verb with ‘transform themselves’. Although either translation is defensible, I submit that Paul’s use of μετασχηματίζω invokes notions of transformation that are key to his rhetorical purposes in 2 Cor. 11, as well as in other parts of 2 Corinthians. I argue that in 2 Cor. 11.13–15, Paul employs ‘transformation discourse’ and that he does so for the purpose of identity-construction. I demonstrate this by situating Paul’s descriptions within ancient transformation traditions and by using positioning theory to analyze his rhetoric. Moreover, reading 2 Cor. 11 in conversation with 2 Cor. 3–4 reveals that Paul uses transformation discourse strategically to differentiate between his and his opponents’ identities. I show that Paul seeks to identify himself as a true apostle, as proven in part by his experience of genuine metamorphosis, and his opponents as deceptive imposters, as shown by the transformation only of their appearances.
Keywords: Transformation; social-scientific methodology; positioning theory; positional identity; Identity; Apostle Paul